Delivering Psychoeducational Results to Parents : A Practitioner's Guide - DeMatteo, Francis J. (New York ; Abingdon, Oxon : Routledge, 2020)
"Delivering Psychoeducational Results to Parents presents a concrete and adaptable feedback model that efficiently communicates complex evaluation results to parents in an easily understandable manner. The book discusses a model rooted in basic learning principles, effective communication practices, and practitioner empathy towards the parent experience of the home-school relationship, hinging upon practitioners and parents jointly creating a permanent product of the evaluation results during the feedback process. It provides early career school psychologists with a parent-friendly feedback model that can be adapted to their school-based setting. The text includes specific verbiage to explaining constructs in the cognitive, achievement, visual-motor, and social-emotional domains, along with considerations in application to working with diverse populations. The text is intended for school psychologists and professionals who complete psycho-educational evaluations for special education eligibility. More specifically, the text is envisioned to support the graduate training of school psychologists and the professional development of early career professionals in the field"--
Chapter 1. Introduction -- Chapter 2. The Feedback Model's Necessity -- Chapter 3. Human Learning -- Chapter 4. Parents and the Feedback Meeting -- Chapter 5. Prerequisite Practitioner Skills to Utilizing the Model -- Chapter 6. Creating a Permanent Product with the Parent: Utilizing the Feedback Model -- Chapter 7. Utilizing the Model with Diverse Populations -- Chapter 8. Application.
OCLC-licensed vendor bibliographic record.
Keywords: School psychology -- Textbooks; Special education -- Parent participation -- Textbooks; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Assessment, Testing & Measurement